Clonal evaluation and recurrent flowering of ornamental pineapple hybrid for use as miniature potted plant - Silva, Bruna de Fátima; Souza, Everton; Dias, Lucas Ezequiel; Silva, Ronilze; Souza, Fernanda (Revista Ciência Agronômica, 2019)
The objective of this study was to evaluate the cloning and recurrent flowering of the miniature pineapple hybrid ORN-MUT based on quantitative and qualitative morphological descriptors for possible use as a potted plant. Besides its reduced size, the ORN-MUT hybrid is notable for its pink fruit, absence of thorns and recurrent flowering at the crown, formed after the plant’s complete cycle (562 days). The hybrid was assessed in the experimental field of the Embrapa Cassava and Fruits research unit in two flowering stages (first flowering and recurrent flowering) and was characterized by quantitative and qualitative morphological descriptors. A joint analysis of the data (multivariate analysis) was performed to verify the distinguishability and uniformity of the clones and parents. ORN-MUT presented uniformity in the first flowering, completing the phenological cycle at 75.70 days (first cycle) and 72.35 days (second cycle) after floral induction, respectively. The recurrent flowering occurred 170.60 days after induction. The peduncle is straight, with average length of 17.80 cm. The syncarp is small and pink, with conical-cylindrical shape. The crown has a moderately sharp tip with greenish central color and pink edges. In the recurrent flowering stage, the plants are smaller, with average size of 24.45 cm. The syncarp is miniaturized, with average of 1.20 layers of fruitlets and length of 1.61 cm. The quantitative and qualitative morphological traits allow classifying the hybrid as a potential potted plant.